2022
DOI: 10.3390/vaccines11010031
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Did Not Increase the Risk of Potentially Related Serious Adverse Events: 18-Month Cohort Study in an Italian Province

Abstract: This cohort study on the entire population of an Italian Province assessed the incidence of potentially vaccine-related serious adverse events (PVR-SAEs) by COVID-19 vaccination status. From January 2021 to July 2022, we extracted all deaths and hospitalizations due to several cardiovascular diseases, pulmonary embolism, and deep vein thrombosis from National Healthcare System official data. During the follow-up, 5743 individuals died, and 2097 were hospitalized for PVR-SAEs. Vaccinated subjects (n = 259,821) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Nevertheless, a recent Italian cohort study demonstrated that vaccinated individuals had a significantly lower all-cause mortality and reduced risk of stroke, thrombo-embolism, and cardiac arrest compared to unvaccinated controls. 20 Although myocarditis is a generally acknowledged, rare side effect of mRNA-based COVID-19 vaccines, and can be complicated by ventricular arrhythmia and SCA/SCD, it is a rather infrequent cause of SCD, 2,3,6,9,10 also in the present study (Tables 1 and 2), and there is currently no evidence to attribute significant numbers of young athlete deaths to this vaccine-induced condition. Male adolescents and male young adults (12-29 years) are mainly affected by myocarditis (incidence 1 in 6,800-35,000), usually 2-4 days after the second mRNA dose.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, a recent Italian cohort study demonstrated that vaccinated individuals had a significantly lower all-cause mortality and reduced risk of stroke, thrombo-embolism, and cardiac arrest compared to unvaccinated controls. 20 Although myocarditis is a generally acknowledged, rare side effect of mRNA-based COVID-19 vaccines, and can be complicated by ventricular arrhythmia and SCA/SCD, it is a rather infrequent cause of SCD, 2,3,6,9,10 also in the present study (Tables 1 and 2), and there is currently no evidence to attribute significant numbers of young athlete deaths to this vaccine-induced condition. Male adolescents and male young adults (12-29 years) are mainly affected by myocarditis (incidence 1 in 6,800-35,000), usually 2-4 days after the second mRNA dose.…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, a recent Italian cohort study demonstrated that vaccinated individuals had a significantly lower all-cause mortality and reduced risk of stroke, thrombo-embolism, and cardiac arrest compared to unvaccinated controls. 20…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility, not discussed, that those who were less affected by the vaccines could have decided to receive the third doses more promptly. As also stated by the authors, further research in the coming years will be required to evaluate the long-term safety of the COVID-19 vaccines [ 202 ]. Other studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective cohort study [25] has been just published on the entire population of the Italian Province of Pescara, where 259,821 subjects were vaccinated with ≥1 dose and 56,494 remained unvaccinated from January 2021 to July 2022. The authors reported much lower rates of all-cause mortality in the vaccinated group.…”
Section: Mortality Data By Vaccination Status From Two Recent Italian...mentioning
confidence: 99%
“…Another limitation is that the study [25] does not seem to have considered the evolution of risks over time. The risks of the vaccinated, expressed as averages over the entire follow-up period, could underestimate those of the last few months of 2022.…”
Section: Mortality Data By Vaccination Status From Two Recent Italian...mentioning
confidence: 99%